2021
DOI: 10.1111/ijfs.15329
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of biofilm formation, adhesion and invasion in Caco‐2 cells by foodborne pathogens using phyto‐mediated synthesised silver nanoparticles from industrial wastes

Abstract: Certain foodborne diseases are associated with antibiotic resistance, a significant problem throughout the world. Silver nanoparticles (AgNPs) using industrial waste from Eucalyptus camaldulensis and sericin, a protein derived from Bombyx mori, were synthesised by a one‐step approach. Spherical‐shaped nanoparticles with the average size of 17.19 nm exhibited strong antioxidant activity. The minimum bactericidal concentrations against foodborne pathogens including Bacillus cereus, Listeria monocytogenes, Staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It has been reported that AgNPs display a potent antibacterial effect against both Gram-negative and the Gram-positive bacteria. 56 However, the antibacterial mechanism of AgNPs is still unclear. The antibacterial action of AgNPs against the Gram-negative bacteria that have a thin peptidoglycan layer may be due to the capability of nanoparticles to penetrate the membrane of the cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that AgNPs display a potent antibacterial effect against both Gram-negative and the Gram-positive bacteria. 56 However, the antibacterial mechanism of AgNPs is still unclear. The antibacterial action of AgNPs against the Gram-negative bacteria that have a thin peptidoglycan layer may be due to the capability of nanoparticles to penetrate the membrane of the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is important to isolate and characterize new lytic phages, especially against this particular pathogen. As other different approaches to control foodborne pathogens (Paosen et al, 2021), phages have proved to be safe to be used in food applications (Sulakvelidze & Barrow, 2005). In addition, phages have the "Generally recognized as safe" (GRAS) status granted by the FDA.…”
Section: Introductionmentioning
confidence: 99%